Literature Review : The Effect of Forensic Audit, Investigative Audit, Judgment Professionalism, Independence and Internal Control on Fraud Disclosure - Della Chastika; Rara Ivanka; M. Fadlan Irfan Damanik; Handriyani Dwilita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze factors that influence fraud disclosure . Fraud, or fraudulent acts, have become a significant problem in various sectors in Indonesia, especially with the dominance of corruption cases. This widespread corruption has a negative impact on the country's economy and public trust in institutions. Previous studies have shown that forensic audits, with an analytical approach to financial evidence, and investigative audits, which focus on thorough investigation procedures, significantly contribute to fraud disclosure. The professionalism of auditor judgment plays a role in ensuring that audit decisions are based on accurate analysis, while auditor independence is important to maintain integrity and objectivity in carrying out audits. In addition, internal control helps prevent and detect fraud early on. This study uses a qualitative method with a literature review approach sourced from trusted journals and scientific publications. The results of the study show that the integration of these factors can increase the effectiveness of fraud disclosure. These findings also emphasize the importance of implementing modern technology, such as big data analytics and artificial intelligence, to strengthen the audit system. The conclusion of this study suggests the importance of a combination of various audit elements to support better organizational oversight. The results of this study indicate that forensic audits, investigative audits, professional judgment, auditor independence, and internal control have a positive effect on fraud disclosure.